The role of behavioral economics in the system of economic sciences - Marchyshyn, Nazar (Herald of Economics, 2023)
Introduction. The article analyzes the theoretical foundations and approaches of behavioral economics in the context of their use in the process of creating information resources for business, considers its content, highlights the key aspects of the impact of the key provisions of behavioral economics on economic science and practice, and also reveals possible prospects for the integration of behavioral economics and accounting information formation processes.The purpose of the article. The purpose of the study is to analyze the key provisions of behavioral economics and their interpretation by scientists, as well as to determine the role of behavioral economics in the context of the development of economic sciences and the possibilities of applying the theoretical postulates of behavioral economics in the process of creating information resources.Methods. To achieve the goal, general scientific methods of cognition were used, namely: monographic and logical analysis, empirical methods of cognition, methods of comparison, extrapolation and generalization. Results. The work of researchers on the main theoretical provisions of behavioral economics as a new trend in economic sciences, which is dynamically developing and focuses on understanding human behavior and decision-making in the real world, is summarized. Research in this area shows that people do not always act rationally, and decisions are often determined by cognitive limitations, psychological factors, and social influences. It was determined that behavioral economics reveals the depths of human rationality, helping to enrich economic science and change the paradigm of decisions made, and therefore, its main provisions can be used in the processes of formation and use of information resources for business.Prospects for further research. Further research can be aimed at implementing the main theoretical provisions of behavioral economics in the processes of forming information arrays for business and developing new theoretical models that would take into account more complex psychological and social aspects of decision-making. This will provide an opportunity to investigate how technology and information influence the decisions of economic agents, as well as the use of information to solve important global problems, such as resource conservation, energy efficiency, combating climate change, social justice, etc.